(NkWANTOWAQ TEORIQ POLQ I TOPOLOGIQ (B/s - (N{WARC(B, (NaLXBERT sOLOMONOWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1989)
(NbIBLIOGR(B.: (NS(B. 397-398s
Keywords: (NkWANTOWAQ TEORIQ POLEJ (B- (NmATEMATI^ESKIE METODYs; (NtOPOLOGIQs